Electrical properties of a-C:H films modified by Pt (International Journal of Mathematics and Physics, 2014)
There have been investigated the conductivity of a-C:H and a-C:H films, obtained by ion-plasmamagnetron sputtering with different substrate temperatures. It is found that the conductivity of a-C:H filmssubstantially dependent on deposition temperature and by changing it from 50 to 200°C conductivity reduced fromabout 10-15 to about 10-2 (ohm • cm)-1. This is due to increase of sp3-hybridized bonds and decrease in concentrationof sp2-hybridized bonds characteristic for graphite (ts = 50°C) and diamond-like (ts = 200°C) a-C:H films structure.Imposition of platinum impurities into the amorphous diamond-like C:H film that were deposited at a temperature of200°C, resulted in substantially, by 13 orders of magnitude, increase in their conductivity. Effect of platinumimpurities on the conductivity of a-C:H film deposited at temperatures of 120 and 50°C are not significant.Analysis of the results for the conductivity of the films using percolation theory shows that the percolation transitionoccurs at concentration of platinum films xc ≈5 at.%.